Reynard's tale : a story of love and mischief - Hatke, Ben (First Second Books, 2023)
Inspired by the 12th century tales of the indomitable trickster fox Reynard, this offbeat tribute to the archetypal rogue has a satisfyingly old-fashioned feeling to it. Although this Reynard adventure is entirely the creation of modern fairytale master Ben Hatke (Mighty Jack), it fits seamlessly into the body of Reynard tales still beloved in Europe to this day. Featuring evocative, charming black-and-white illustrations and a swiftly moving narrative, Reynard's Tale follows our hero through a series of encounters with other classic figures from this body of folklore to piece together a headlong journey through a perilous landscape filled with murderers, kings, ex-lovers, mermaids, and even Death herself.